IMF Staff Papers : Volume 2, No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1952)
This paper discusses various foreign payments practices in the United States. Most foreign payments in the United States are, therefore, done along traditional lines in whatever manner. Several nontraditional practices, however, have developed in recent years as the result of trade and payments restrictions established by foreign Governments. The amount and type of exchange sold by the US banks to their customers are limited only, if at all, by regulations abroad or by the banks' own limitations. In making or receiving foreign payments, the US banks deal generally with three types of customers which are, in the order of their importance: exporters and importers, individuals or corporations desiring to make or receive nontrade financial payments, and speculators. Foreign payments for account of individuals are usually small individually however, in the aggregate, they represent an important function of the banks located in the larger cities with a considerable foreign-born population.